Dermatoscopy in diagnosing maculopapular cutaneous mastocytosis - Popadić Mirjana (Praxis Medica, 2016)
The diagnosis of cutaneous mastocytosis is based on the clinical finding of the pigmented macules or papules, positive Darier's sign and a dermal infiltrate composed of mast cells that can be better visualized by the use of special stains (Giemsa or Toluidine blue). Clinical, dermatoscopic and histopathological presentations of new appearing pigmented lesions in a female patient were presented. Dermatoscopic findings of pigment network-like structure combined with parallel pigmented lines and central reddish background in a adult patient with new appearing pigmented lesions should led us to searching for cutaneous mastocytosis.